Integrative neural mechanisms for social communication of learned vocal behavior - Anderson, Katherine L.; Whitney, Osceola (Frontiers in Integrative Neuroscience, 2025)
Context-sensitive behaviors are crucial for the adaptive success of many organisms. Investigating neural processes that facilitate context-sensitive behavior requires knowledge of the molecular signaling and anatomical brain connectivity within and between relevant brain networks. Here, we outline the roles of oxytocin and dopamine signaling systems in context-sensitive singing in songbirds. Additionally, using the recently compiled songbird connectome, we review anatomical connectivity between vocal-motor and social brain networks that may facilitate context-sensitive singing. We present a model for context-sensitive adaptability of singing behavior in songbirds. We propose that the medial preoptic nucleus of the hypothalamus may serve as the output nucleus of the social behavior network, influencing oxytocin-mediated dopamine delivery to the vocal control network, in a context-sensitive manner. As many components of this model are conserved across species, we speculate that this proposed model can be generalized to facilitate context-sensitive motor behaviors across vertebrate species. Overall, we emphasize the importance of investigating each component of our proposed model, within a single species. This perspective aims to uncover how integrated neural mechanisms give rise to behavior.